Radiomics in head and neck cancer: from exploration to application - Wong, Andrew J.; Kanwar, Aasheesh; Mohamed, Abdallah S.; Fuller, Clifton D. (Translational Cancer Research; Vol 5, No 4 (August 08, 2016): Translational Cancer Research (Focused Issue: Radiomics in Radiation Oncology), 2016)
In the context of clinical oncology, a fundamental goal of radiomics is the extraction of large amounts of quantitative features whose subsequent analysis can be used for decision support towards personalized and actionable cancer care. Head and neck cancers present a unique set of diagnostic and therapeutic challenges by nature of its complex anatomy and heterogeneity. Radiomics holds the potential to address these barriers, but only if as a collective field we direct future effort towards investigating specific oncologic function and oncologic outcomes, with external validation and collaborative multi-institutional efforts to begin standardizing and refining radiomic signatures. Here we present an overview of radiomic texture analysis methods as well as the software infrastructure, review the developments of radiomics in head and neck cancer applications, discuss unmet challenges, and propose key recommendations for moving the field forward.